JURIDICAL ANALYSIS OF PUBLIC INFORMATION DISCLOSURE IN GOVERNMENT SYSTEMS IN THE DIGITAL ERA - Suud Sarim Karimullah; Arif Sugitanata; Fawwaz Elmurtadho (UIN Kiai Haji Achmad Siddiq Jember, 2023)
This article conducts a juridical analysis of public information disclosure in government systems in the digital era. The purpose of compiling this article is to identify legal issues related to public information disclosure in the digital era and provide appropriate legal solutions to overcome these problems. The research method used is a literature study by analyzing laws and regulations related to public information disclosure, as well as collecting the latest data and information about the use of information technology in government in a descriptive-analytical manner. The study results show that public information disclosure is a basic principle in a democratic government system that is fundamental for strengthening government accountability and encouraging public participation in policy-making. In the digital era, public information disclosure is becoming increasingly important, but it also requires the protection of information security and privacy because public information disclosure in the digital era has complex legal implications, such as issues of information security, personal data protection, and copyright issues. This article suggests that the government strengthen regulations regarding public information disclosure in the digital era, including developing strict information security standards and protecting intellectual property rights. In addition, the government also needs to increase public awareness about their right to obtain public information and develop an effective and efficient information system to facilitate access to public information.